Program Pendampingan PPG di UIN Sunan Kalijaga: Langkah Menuju Guru Profesional - Indriyani Ma'rifah (PaKMas: Jurnal Pengabdian Kepada Masyarakat, 2024)
The purpose of this community service project is to provide support to students enrolled in the Teacher Professional Education (PPG) program at UIN Sunan Kalijaga's Teacher Training and Education Institute (LPTK). This support aims to offer academic, emotional, and social assistance to the students. The method used involves virtual mentoring through various digital platforms such as the Learning Management System (LMS) SPACE, Zoom Meeting, Google Meet, WhatsApp, YouTube Live Streaming, and Telegram. The mentoring programs are conducted in stages and tailored to the students' needs, including Virtual Hotline Services (VHS), facilitator support, precondition learning at each stage, video media development, material deepening refreshment, exam outline analysis, and try outs (TO). The results show a very high graduation rate, reaching 98.1%, which indicates the success of the mentoring program. This achievement can serve as a model for other Teacher Training Institutes (LPTKs) to improve the quality of support and mentoring for PPG participants, ultimately helping them become professional teachers.